PENGARUH KOMPENSASI TERHADAP KINERJA DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING (Studi Pada Pegawai Puskesmas Se-Kabupaten Lombok Timur) - SUPRIANDI SUPRIANDI (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2016)
Public Health Centers is a technical implementation unit under the District Health Agency that is responsible to conduct health development in a region. To achieve the development vision and mission in health, Health Centers are supported by sufficient resources such as capital, material, machine and human resources. Based on the evaluation of health center performance in 2014, all are good. The condition described for the performance of employees of Health Centers in East Lombok analyzed based on the presence list showed that the level of participation is 98%. The performance and satisfaction of health centers may be affected by the good compensation in Health Centers.This research is aimed at determining the effect of compensation on the performance of employees through the work satisfaction in health centers in East Lombok. This research is a explanatory qualitative study. The samples were 70 respondents selected through cluster random sampling and the data were analyzed using Path Analysis.The research showed that (1) Compensation does not affect directly the performance of employees; (2) Compensation affects directly the work satisfaction of employees; (3) Work satisfaction affects directly the performance of employees; (4) Compensation has direct effect on the performance of employees of Health centers through work satisfaction in East Lombok.Keywords: Compensation, Work Satisfaction, Performance.